2010
DOI: 10.14214/sf.455
|View full text |Cite
|
Sign up to set email alerts
|

Model computations on the climate change effects on snow cover, soil moisture and soil frost in the boreal conditions over Finland

Abstract: This study considered how climate change affects the accumulation of snow, the soil moisture and soil frost at sites without tree cover in boreal conditions in Finland (60°-70°N). An increase of 4.5 °C in annual mean temperature and 20 % in annual precipitation were assumed for Finland by the year 2100 according to A2 emission scenario. Along with climate, the soil type of the permanent inventory plots of the Finnish National Forest Inventory was used. Soil and climate data were combined by using a process-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 18 publications
(20 reference statements)
2
47
0
Order By: Relevance
“…In accordance with previous studies (Venäläinen et al, 2001a(Venäläinen et al, , 2001bKellomäki et al, 2010), our results suggest that climate warming will lead to shorter soil frost periods reducing wintertime ground-bearing capacity. The projected decrease in the wintertime bearing season length was similar in the studied two climate model ensembles.…”
Section: Evaluations Of Main Results and Their Implications To Forestsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous studies (Venäläinen et al, 2001a(Venäläinen et al, , 2001bKellomäki et al, 2010), our results suggest that climate warming will lead to shorter soil frost periods reducing wintertime ground-bearing capacity. The projected decrease in the wintertime bearing season length was similar in the studied two climate model ensembles.…”
Section: Evaluations Of Main Results and Their Implications To Forestsupporting
confidence: 93%
“…The climate warming is expected to be pronounced on high latitudes like in Finland (Räisänen and Ylhäisi, 2015;Ruosteenoja et al, 2016). Previous studies have indicated that the climate warming leads unsurprisingly to reduced soil frost depth and shorter soil frost periods (Venäläinen et al, 2001a(Venäläinen et al, , 2001bKellomäki et al, 2010;Jungqvist et al, 2014). This may shorten the winter harvesting season with good ground-bearing capacity, particularly on drained peatlands, having thus mainly negative impact on the forestry sector.…”
mentioning
confidence: 99%
“…On the other hand, increased precipitation in areas where temperatures remain below freezing can give longer-lasting snow cover in some areas (Johansson et al, 2011). Less snow cover can increase the occurrence, depth and duration of soil frost due to less insulation (Källomäki et al, 2010;Bjerke et al, 2015), and was shown to affect annual productivity of grasslands in Canada and Germany (Vankoughnett et al, 2016;Zeeman et al, 2017). There has been an increase in frequency of winter warming events in northern Norway, Sweden, and Finland during the last 50 years (Vikhamar-Schuler et al, 2016).…”
Section: Forage Dry Matter Productivitymentioning
confidence: 99%
“…Gonthier et al, 2005;La Porta et al, 2008;Müller et al, 2014). The effect of strong winds on forests is expected to increase due to the shorter frozen soil period that currently improve tree anchorage during the winter months (Blennow et al, 2010;Kellomäki et al, 2010;Gregow et al, 2011). Bark beetles are expected to benefit from the warmer temperatures by increased reproduction and having more generations with full life cycles (Bale et al, 2002).…”
Section: Norway Spruce and The Key Disturbancesmentioning
confidence: 99%